Computer and cell phone access for individuals with mobility impairments: An overview and case studies. - Gentry, Tony; Burgstahler, Sheryl; Comden, Dan; Lee, Sang-Mook; Arnold, Anthony; Brown, Kayla (NeuroRehabilitation, 2011)
Computers, telephones, and assistive technology hold promise for increasing the independence, productivity, and participation of individuals with disabilities in academic, employment, recreation, and other activities. However, to reach this goal, technology must be accessible to, available to, and usable by everyone. The authors of this article share computer and telephone access challenges faced by individuals with neurological and other impairments, assistive technology solutions, issues that impact product adoption and use, needs for new technologies, and recommendations for practitioners and researchers. They highlight the stories of three individuals with neurological/mobility impairments, the technology they have found useful to them, and their recommendations for future product development.